High platelet-to-albumin ratio is associated with 30-day mortality in critically ill patients - Chun-Lin Liu; Qing-Nian Wu; Zhi-Ying Deng; Ping Chen; Shi-Qiang Guo (European Journal of Medical Research)
Abstract Background The role of inflammation and hypoproteinemia in influencing outcomes of critically ill patients has been widely recognized. However, there is a paucity of research on the prognostic value of the platelet-to-albumin ratio (PAR) in critically ill patients. Therefore, the aim of this study is to assess the prognostic significance of PAR in this population. Methods Patients diagnosed with critical illnesses from January 2020 to October 2022 were retrospectively enrolled in our study. Baseline demographic and clinical data were collected for each participant. Platelet counts and albumin levels were measured at baseline, and the PAR was calculated. The area under the receiver operating characteristic curve, Kaplan–Meier survival analysis, and multivariate Cox regression analysis were used to predict 30-day mortality. Results Three hundred and seventy-eight patients diagnosed with critical illness were categorized into two groups: survivors (n = 299) and non-survivors (n = 79). Analysis of the 30-day outcome revealed that the area under the curve (AUC) for the PAR (AUC: 0.705; 95% CI 0.639–0.771; p < 0.001) was significantly higher than that for albumin (AUC: 0.673; 95% CI 0.609–0.736; p < 0.001), but slightly lower than that for the APACHE II score (AUC: 0.713; 95% CI 0.650–0.777; p < 0.001). In addition, the Kaplan–Meier survival analysis demonstrated a significantly higher 30-day mortality in the high-PAR group. Furthermore, Cox regression analysis identified albumin (HR: 0.936; 95% CI 0.895–0.978; p = 0.003), APACHE II score (HR: 1.225; 95% CI 1.149–1.305; p < 0.001), and high PAR (HR: 1.237; 95% CI 1.130–1.353; p < 0.001) as independent risk factors for the prognosis of critically ill patients. Conclusions The PAR has emerged as a significant prognostic indicator in critically ill patients, with an elevated ratio being associated with poorer clinical outcomes.